2010
DOI: 10.1200/jco.2009.24.9557
|View full text |Cite
|
Sign up to set email alerts
|

Alberta Physical Activity and Breast Cancer Prevention Trial: Sex Hormone Changes in a Year-Long Exercise Intervention Among Postmenopausal Women

Abstract: A B S T R A C T PurposeWe examined how an aerobic exercise intervention influenced circulating estradiol, estrone, sex hormone-binding globulin (SHBG), androstenedione, and testosterone levels, which may be involved in the association between physical activity and breast cancer risk. MethodsA two-center, two-arm randomized controlled trial of exercise was conducted in 320 postmenopausal, sedentary women age 50 to 74 years. Participants were randomly assigned to a 1-year aerobic exercise intervention of 225 min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
239
1
6

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 196 publications
(252 citation statements)
references
References 34 publications
6
239
1
6
Order By: Relevance
“…All participants provided signed informed consent. The study design and methods for the ALPHA Trial have been previously described (30). In brief, a 2-centered, 2-armed, yearlong, randomized controlled exercise intervention trial was conducted between 2003 and 2006 in Calgary and Edmonton, Alberta, Canada among 320 postmenopausal healthy women.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All participants provided signed informed consent. The study design and methods for the ALPHA Trial have been previously described (30). In brief, a 2-centered, 2-armed, yearlong, randomized controlled exercise intervention trial was conducted between 2003 and 2006 in Calgary and Edmonton, Alberta, Canada among 320 postmenopausal healthy women.…”
Section: Methodsmentioning
confidence: 99%
“…Here, we describe the effect of our intervention on inflammatory biomarkers; namely, circulating CRP, IL-6, and TNF-a, which were secondary outcomes from the trial. The primary outcomes of the trial, endogenous sex hormone (30), and adiposity changes (31), have been previously reported.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, the SHAPE trial showed that relative to controls, androgen (but not estrogen) levels decreased significantly in exercisers who lost >2% body fat after 4 months of exercise (Monninkhof et al 2009). In the ALPHA trial, estrogen levels decreased significantly more in exercisers than in controls after 12 months, even after adjusting for weight change, whereas androgen levels did not change significantly (Friedenreich et al 2010a). Unlike the first two trials, the ALPHA trial findings for estrogen suggest an independent role for physical activity.…”
Section: Sex Hormonesmentioning
confidence: 68%
“…Three randomized, controlled trials (RCTs) that were specifically designed to examine the etiologic pathways between physical activity and postmenopausal breast cancer risk have been conducted (Friedenreich et al 2010a;McTiernan et al 1999;Monninkhof et al 2007b). These studies have involved supervised, controlled exercise interventions in which several proposed breast cancer biomarkers were measured and compared between the exercise and control groups to assess the impact of exercise on these biomarkers.…”
Section: Summary Of Epidemiologic Findingsmentioning
confidence: 99%
See 1 more Smart Citation